Simulative Study into the Development of a Hybrid HVDC System Through a Comparative Research with HVAC: a Futuristic Approach - Narayan, R. S.; Mohan, S.; Sunitha, K. (Engineering, Technology & Applied Science Research, 2017)
High Voltage Direct Current Transmission (HVDC) is considered a better solution for bulk long distance transmissions. The increased use of HVDC is a result of its advantages over the HVAC systems and especially of its fault stability nature. A better solution is proposed by using a Voltage Source Controlled–HVDC as one of the infeed for the Multi-Infeed HVDC (MIDC or MI-HVDC) systems. The main advantage with the VSC converter is its flexible power control which enhances the stability of the MIDC systems. In this paper, the behavior of an HVDC system is compared with that of an HVAC during faults. A Hybrid HVDC system that includes a LCC as a rectifier unit and a VSC converter as the inverter is being proposed. It is considered suitable for MIDC systems and particularly for supplying a weak AC system. The performance of the system during steady state and transient conditions for all the proposed topologies including HVDC, HVAC and Hybrid HVDC are studied in MATLAB/SIMULINK. All of the proposed control strategies are evaluated via a series of simulation case studies.